RANCANG BANGUN SISTEM INFORMASI MANAJEMEN PRODUKSI IKLAN BERBASIS WEB - Yosua Hagia Remindauw; Fitro Nur Hakim (JURNAL TEKNIK INFORMATIKA DAN MULTIMEDIA, 2022)
Production Managemen System at Radio Rhema Media Jaya Perkasa Company still takes a long time and executes manually. The manual production system consists of the use of paper forms, uncentralized data, and direct interactions within divisions, all of which directly affects the commercial productions. In the old system, time needed for a commercial production starting from gathering the materials until the commercial is ready to be broadcasted is approximately 5 days. The method used in this research is SDLC (System Development Life Cycle) but the last step is excluded. The result of the research is a Management Production Information System Web – based which facilitates marketing, financing/administation, production, and broadcasting divisions in Radio Rhema Media Jaya Perkasa Company to manage commercial productions including getting commercial orders, obtaining sales orders, broadcasting scheduling, as well as issuing reports on commercial production in a faster and more convinient manner.